A NEW SCALARIZING APPROACH AND THE SEMICONTINUITIES OF THE SOLUTION MAPPING OF A PARAMETRIC VECTOR QUASI-EQUILIBRIUM PROBLEM - Phạm Hữu Sách; Lê Anh Tuấn (Tạp chí Khoa học Đại học Đà Lạt)
This paper gives sufficient conditions for the upper and lower semicontinuities of the solution mapping of a parametric vector quasi-equilibrium problem with moving cones. We use a new scalarizing approach quite different from traditional linear scalarization approaches. The main tool of this paper is a new notion of nonlinear scalarization function which is a generalised version of the Gerstewitz function applied to set-valued maps.